PRAKTIKALITAS E-LKPD BERBASIS PROBLEM BASED LEARNING PADA MATERI PELUANG KELAS X - Himatul Anisah; Rahmi Rahmi; Alfi Yunita (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This research aims to determine the level of practicality of E-LKPD based on problem based learning on opportunity material for class X. This research is expected to help students learn independently and improve problem solving. This type of research is development research (Research and Development) using the ADDIE development model which consists of 5 processes, namely the analysis process (Analysis), the design process (Design), the development process (Development), the implementation process (Implementation), and the evaluation process ( Evaluation). The subjects of this research were Phase E students of SMA Negeri 1 Bungo for the 2023/2024 academic year. The instruments in this research were questionnaires, interview guides, and learning outcomes tests. The practicality results in this research were 92.2% in the very practical category.